Melanomas Arising on Skin With Chronic Sun-Induced Damage Exhibit Low Degree of Angiogenesis and Lymphangiogenesis. (June 2015) - Pastushenko, Ievgenia; Vicente-Arregui, Sandra; Van den Eynden, Gert G.; Gracia-Cazaña, Tamara; Carapeto, Francisco J.; Alvarez-Alegret, Ramiro; Dirix, Luc Y.; Vermeulen, Peter B.; Van Laere, Steven
Abstract : Abstract: Differences in gene expression between melanomas arising on skin intermittently and chronically sun-exposed areas were described. Additionally, several studies have shown differences in clinical characteristics and prognosis, suggesting distinct biological pathways in the development of these tumors. We performed a retrospective investigation aimed on evaluation of the differences in angiogenesis and lymphangiogenesis between melanomas arising on skin with and without signs of chronic sun-induced damage. For that purpose, we evaluated relative blood and lymphatic vessel areas, blood and lymphatic endothelial cell proliferation fractions, separately for peritumoral and intratumoral areas. We have shown that melanomas arising on sun-exposed skin exhibit lower angiogenic and lymphangiogenic potentials and better prognosis than those arising on skin without signs of chronic sun-induced damage.